Factors Influencing the Quality Management of the Private Medical Consulta-tion of the City of Trujillo (SCIÉNDO INGENIUM, 2021)
The research was proposed as a general objective to identify the factors that influence the quality management of the private medical consultation of the city of Trujillo. The study sample included 173 patients who were treated in a private medical consultation in the city of Trujillo, during the period June - July 2017. The information was collected through structured questionnaires based on the SERVPERF questionnaire. It was determined that the level of perceived quality by the patients of the private medical consultation in the city of Trujillo during the months of June - July 2017 is medium level (52.6%) with a greater tendency to the Low Medium Level (277%) and 23.1% perceives a high quality level in the private medical consultation of the city of Trujillo. Finally, according to 82.6% of the patients, there are 04 factors that influence the quality management of the private medical consultation in the city of Trujillo: Physician, Assistant Personnel, Physical Facilities and Image elements.
Keywords: quality management; private medical consultation; factors